The Tar Heel state a history of North Carolina - Ready, Milton (Univ. of South Carolina Press, 2005)
From the Publisher: In the last three decades North Carolina has witnessed a remarkable growth in population, economic development, and political importance, and it now ranks as the tenth most populous state in the Union. The Tar Heel State: A History of North Carolina constitutes the most comprehensive and inclusive single-volume chronicle of the state's storied past to date, culminating with an attentive look at recent events that have transformed North Carolina into a southern megastate. Integrating tales of famous pioneers, statesmen, soldiers, farmers, captains of industry, activists, and community leaders with more marginalized voices, including those of Native Americans, African Americans, and women, Milton Ready gives readers a view of North Carolina that encompasses perspectives and personalities from the coast, "tobacco road," the piedmont, and the mountains in this sweeping history of the Tar Heel State